The Role of Screen Time, Digital Interaction, and Social Support in Adolescent Psychological Well-Being: A Systematic Literature Review of Adolescent Digital Well-Being - Rahma Zikra; Layyinah (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2025)
This study examines the relationship between gadget use and psychological well-being in adolescents through a Systematic Literature Review (SLR) approach. The research focuses on four core aspects: the duration of screen time, the quality of digital interaction, the protective roles of social support and digital literacy, and the differential impacts of social media and video games on adolescent psychological well-being. Sixteen journal articles that met the inclusion criteria were systematically extracted from the Scopus database and synthesized using the PRISMA protocol to ensure methodological rigor, transparency, and replicability. The results indicate that screen time has a dynamic and non-linear association with psychological well-being. While excessive and uncontrolled usage is associated with heightened risks of anxiety, depression, and reduced life satisfaction, moderate use accompanied by meaningful digital engagement contributes positively to emotional resilience, self-regulation, and social connectedness. Furthermore, protective factors—particularly family support, peer relationships, and digital literacy—were found to mediate and moderate the effects of digital interaction, transforming potentially negative outcomes into opportunities for psychological growth. The findings also reveal distinct impacts across digital platforms: social media is closely related to identity formation and social validation, while video games are linked to cognitive engagement and recreational coping. This review introduces an integrative conceptual model that positions digital interaction not solely as a risk factor, but as a dual pathway with both adaptive and maladaptive outcomes depending on the presence of moderating variables. These findings contribute to theoretical advancements in digital well-being and offer practical guidance for the development of culturally responsive interventions in educational and family settings.